Family functionality as a mediator in the relationship between humanization and academic burnout in adolescents - Pablo Molina Moreno; Silvia Fernández Gea; María del Carmen Pérez-Fuentes; María del Mar Molero Jurado; José Jesús Gázquez Linares (Frontiers in Psychology)
IntroductionDuring adolescence, personal competencies serve as protective factors against social exclusion and are crucial for promoting psychological well-being and creating opportunities for growth. Family and educational systems play a pivotal role in supporting these competencies. This study aims to analyze the relationships between humanization competencies, academic burnout, and family functionality, to examine sex differences in these variables, and to explore the mediating effect of family functionality.MethodsThe sample comprised 1,092 secondary school students (584 females and 508 males) from Almería, Spain, aged 12 to 17 (M = 14.5 years).ResultsThe findings show that family functionality is positively associated with humanization competencies and academic efficacy, and negatively associated with emotional exhaustion and cynicism. Notable sex differences emerged, with males scoring higher in optimism, self-efficacy, and affect, while females scored higher in sociability and cynicism. Mediation analysis revealed that family functionality partially mediates the relationship between humanization competencies and academic burnout, specifically impacting cynicism, academic efficacy, and emotional exhaustion.DiscussionThese results highlight the critical role of a supportive family environment in enhancing adolescents’ psychological resilience and academic outcomes. The study suggests that interventions targeting family functionality could be effective in reducing academic burnout and promoting overall well-being among adolescents.